Analisis Literasi Numerasi Mahasiswa Pendidikan Biologi Berdasarkan Asesmen Kompetensi Minimum - Ramadhan, Fitra; Purnomo, Miko; Ruron, Antonius Tuan Tana; Tampubolon, Jonris (Biocaster : Jurnal Kajian Biologi, 2025)
The development of the Industrial Revolution 5.0 requires students, particularly prospective biology teachers, to acquire 21st-century skills, including numeracy literacy, which serves as the foundation for critical thinking, analytical reasoning, and problem-solving. This study aims to analyze the numeracy literacy profile of Biology Education students based on the Minimum Competency Assessment (AKM). The research employed a quantitative descriptive method involving 88 first- and third-semester students of the Biology Education Study Program at the University of Timor, selected using purposive sampling. The research instrument consisted of a numeracy test that referred to the content, context, cognitive processes, and numeracy literacy levels of the AKM. The findings reveal that students’ numeracy literacy is still categorized as Requiring Special Intervention. This condition is influenced by memorization-oriented learning, low learning motivation, and limited integration of numeracy in biology instruction. These results highlight the importance of implementing innovative and contextual learning strategies integrated with numeracy literacy so that prospective biology teachers can not only meet the minimum AKM standards but also develop pedagogical competencies relevant to the challenges of the 21st century.